Peri-ventricular grey stimulation versus motor cortex stimulation for post stroke neuropathic pain. - Nandi, D; Smith, H; Owen, S; Joint, C; Stein, J; Aziz, T (2002)
Central post stroke pain is often difficult to manage satisfactorily with conventional treatment modalities for pain. In the last decade functional neurosurgery has offered hope with motor cortex stimulation achieving significant alleviation of pain in some patients. Unfortunately this has led to the neglect of chronic stimulation of deep grey matter as another modality of treating this condition. In this article we present our experience with motor cortex stimulation and that with deep grey matter stimulation in patients with post stroke pain. We argue that both modalities have a significant role and that what is required are better methods of identifying particular patients who are more likely to respond to one or the other.